The Effect of Shooting Drill Training Model on Basketball Shooting Skills of Extracurricular Students at SMPN 3 Kadipaten - Wijaya, Zidan Rizky; Lengkana, Anggi Setia; Supriyadi, Tedi (UNIVERSITAS NEGERI MAKASSAR, 2025)
The drill training model is typically applied in focused training to enhance technique. This training model is rarely implemented in extracurricular activities. Therefore, research needs to be conducted on the drill training model as a method to improve students' shooting skills. This research aims to determine the effect of the drill training model on the shooting skills of students at SMPN 3 Kadipaten in basketball games. The method used in this research is a one-group pretest-posttest design where a sample of 20 students is selected using proportionate random sampling. The instrument that will be applied in this research is a treatment focused on students' shooting practice. The results show that there is a significant effect of the shooting drill training method on students' shooting skills, which can be seen through the T-test. For the pretest data, the t-value is 5.080 with 19 degrees of freedom (df) and a significance (Sig.) of 0.000. Meanwhile, for the posttest data, the t-value is 9.114 with 19 degrees of freedom (df) and a significance (Sig.) also of 0.000. Since the significance value is less than 0.05, the null hypothesis (Ho) is rejected.